Strategic Communication Design for enhanced MHHM Practices among School Girls in Tamil Nadu - Prabha R, Rama; R, Reshithalakshmi; Aldo J, Jeffrin (Journal of Neonatal Surgery, 2025)
Menstrual health is more than just a hygiene issue—it’s a matter of dignity and empowerment. In Tamil Nadu, adolescent girls continue to face stigma, misinformation, and a lack of basic facilities when it comes to managing their periods. This study explores how strategic communication can help close these gaps. We conducted a mixed-methods study involving 750 schoolgirls across six districts in Tamil Nadu, and implemented a communication intervention among selected students. The results showed that culturally sensitive communication, especially when delivered through trusted channels like schools, significantly improved menstrual knowledge and practices. This paper advocates for enhanced menstrual education, improved infrastructure, and robust policies to support girls during a natural and critical phase of their lives.